2023
DOI: 10.3390/su151511513
|View full text |Cite
|
Sign up to set email alerts
|

Endogeic Earthworms Avoid Soil Mimicking Metal Pollution Levels in Urban Parks

Abstract: In response to long-lasting high levels of metallic trace elements (MTEs) in urban soils, we expect soil invertebrates inhabiting urban environments to have evolved detection and avoidance and/or tolerance mechanisms to MTE pollution. In this study, I used artificial soils with concentrations of lead, zinc, copper, chromium and nickel that reflect pollution levels in the soils of Parisian parks. Using choice experiments, I compared habitat preference (i.e., the occurrence of individuals in the polluted vs. unp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 60 publications
(78 reference statements)
1
5
0
Order By: Relevance
“…The mean concentrations observed in our study closely resemble those obtained in 2015 by Foti and colleagues across 30 urban lawns in Paris (Foti et al, 2017). These elements are characteristic of urban soils (Ajmone-Marsan and Biasioli, 2010; Cachada et al, 2013;Chatelain, 2023;Foti et al, 2017) where they accumulate due to various anthropogenic sources, including the combustion of fossil fuels, waste incineration, or the production of alloys (e.g. brass), paints, batteries, or tires (Binner et al, 2023).…”
Section: Variation In Mte Levels In Urban Lawnssupporting
confidence: 87%
See 4 more Smart Citations
“…The mean concentrations observed in our study closely resemble those obtained in 2015 by Foti and colleagues across 30 urban lawns in Paris (Foti et al, 2017). These elements are characteristic of urban soils (Ajmone-Marsan and Biasioli, 2010; Cachada et al, 2013;Chatelain, 2023;Foti et al, 2017) where they accumulate due to various anthropogenic sources, including the combustion of fossil fuels, waste incineration, or the production of alloys (e.g. brass), paints, batteries, or tires (Binner et al, 2023).…”
Section: Variation In Mte Levels In Urban Lawnssupporting
confidence: 87%
“…Interestingly, while Pižl and Josens concluded in their study that soil pollution levels in Brussels did not significantly shape the composition of earthworm communities, their results clearly show that the earthworm community at the site with the highest concentration of Cu in the soil (28.83 mg/kg) was dominated by A. chlorotica (Pižl and Josens, 1995). Although this outcome might imply that A. chlorotica has a higher tolerance to Cu pollution, earlier research indicated that this species is one of the most susceptible to MTE pollution (Chatelain, 2023;Nahmani et al, 2003;Spurgeon and Hopkin, 1996). For example, when subjected to soil containing a blend of Zn, Pb, Cu, Cr, and Ni, designed to simulate pollution levels found in urban environments, several A. chlorotica individuals died, while no casualty was measured in the two other earthworm species studied (Chatelain, 2023).…”
Section: Earthworm Community Response To Mte Levelsmentioning
confidence: 83%
See 3 more Smart Citations